Variation in Ultraviolet (UV-C) Contact Time Using Solar Panels on the Reduction of Total Coliform in Clean Water at PT. X, Sumedang Regency - Kaniawati, Nina; Iqbal, Muhamad; Bambang Purnama, Lubis; Yety Hanurawaty, Neneng (Poltekkes Kemenkes Palu, 2025)
Background: Water contaminated with Total Coliform can lead to diseases such as diarrhea, cholera, dysentery, and other gastrointestinal infections. Preliminary testing of water at PT. X revealed a Total Coliform count of 56 CFU/100 ml, surpassing the safe threshold for clean water. This study aims to evaluate the effect of varying ultraviolet (UV-C) light contact times—90, 120, and 150 seconds—on the reduction of Total Coliform in clean water. Methods: An experimental post-test with a control group design was used. The sample size was determined by the number of treatment groups and repetitions, resulting in a total of 24 samples. Grab sampling was employed for sample collection. Results: The average Total Coliform count in the control group was 56 CFU/100 ml. After UV-C treatment, the counts decreased to 32 CFU/100 ml at 90 seconds, 11 CFU/100 ml at 120 seconds, and 0 CFU/100 ml at 150 seconds. One-way ANOVA analysis yielded a p-value of 0.000, indicating a significant effect of UV-C contact time on the reduction of Total Coliform in clean water at PT. X, Sumedang Regency. Conclusion: Disinfection using UV-C light with a contact time of 150 seconds is recommended